FORMULATION OF LIPS BALSAM FROM RED DRAGON FRUIT EXTRACT (Hylocereus polyrhizus) - Amelia Sari; Meisya Raihan; Nurmalia Zakaria; Rima Hayati; Ernita Silviana (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
Lip balm is a moisturizer used as a lip balm. Red dragon fruit skin has anthocyanin as an antioxidant and protects against free radicals. The aim is to formulate red dragon fruit extract on the skin in the form of lip balm which has physical and safety characteristics. Red dragon fruit extract on the skin used in lip balm preparations, namely 0%, 5%, 10% and 15%. Evaluation of the lip balm including organoleptic, homogeneity, smearability, pH got good results and irritation test showed that all lip balm concentrations were safe to use because there was no reaction. So that the red dragon fruit extract on the skin can be used as a lip balm preparation. The difference in the concentration of red dragon fruit extract on the skin does not affect the physical properties of the lip balm preparation.